2015
DOI: 10.1093/jxb/erv111
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of the cotton endo-1,4-β-glucanase gene KOR1 disrupts endosperm cellularization, delays embryo development, and reduces early seedling vigour

Abstract: HighlightTransgenic evidence is provided that the expression of a cotton endo-1,4-β-glucanase, GhKOR1, is required for endosperm cellularization, cotton fibre cellulose synthesis, and the establishment of seedling vigour

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The total RNA was extracted from different tissues, including roots, stems, and leaves using the cetyltrimethyl ammonium bromide-acid phenol method (Shang et al, 2015). First-strand cDNA was generated using HiScript Q RT SuperMix for qPCR (+gDNA wiper) (Vazyme) according to the manufacturer's instructions.…”
Section: Rna Extraction and Qrt-pcrmentioning
confidence: 99%
“…The total RNA was extracted from different tissues, including roots, stems, and leaves using the cetyltrimethyl ammonium bromide-acid phenol method (Shang et al, 2015). First-strand cDNA was generated using HiScript Q RT SuperMix for qPCR (+gDNA wiper) (Vazyme) according to the manufacturer's instructions.…”
Section: Rna Extraction and Qrt-pcrmentioning
confidence: 99%
“…Recent RNAi and co-suppression mediated down regulation study toward investigating the potential function of cotton KORRIGAN ( GhKOR1 ), a highly conserved membrane-bound endoglucanase, has resulted in smaller filial tissue and reduced seed weight, leading to various abnormalities in endosperm formation and delayed embryo development. Results collectively suggested that the GhKOR1 gene is required for the development of viable cottonseed with normal seed germination and seedling growth ( Shang et al, 2015 ). Another interesting RNAi gene silencing study targeting cotton acyl-CoA N-acyltransferase (EC 2.3; GhACNAT ) using VIGS resulted in abnormal anther formation and sterile plants.…”
Section: Rnai For Fertility and Embryogenesis Studiesmentioning
confidence: 99%
“…Aniline blue was prepared in water at 0.05% (w/v) and stored in the dark at 4°C. Free-hand sections (;1 mm) of seeds were produced and stained with aniline blue for 10 min in the dark, followed by a 30-s wash with water (Shang et al, 2015). Fluorescent signals from aniline blue were observed under a Zeiss LSM780 confocal microscope using a 405-nm excitation laser (Benitez-Alfonso et al, 2013).…”
Section: Aniline Blue Staining Electron Microscopy Of Pd Structure mentioning
confidence: 99%
“…Seeds fixation and embedding were performed as described by Shang et al (2015). Cotton seeds (5 DPA) were fixed in 2% (v/v) paraformaldehyde and 0.1% (v/v) glutaraldehyde in phosphate buffer (25 mM, pH 7.2) for 2 h. The seeds were dehydrated in a step-graded ethanol series and embedded in LR White resin (medium grade; Alltech) through a step-graded series after washing in buffer.…”
Section: Aniline Blue Staining Electron Microscopy Of Pd Structure mentioning
confidence: 99%